Nucleoid-Associated Protein HU: A Lilliputian in Gene Regulation of Bacterial Virulence - Stojkova, Pavla; Spidlova, Petra; Stulik, Jiri (Frontiers in Cellular and Infection Microbiology, 2019)
Histone-like proteins are group of small but abundant proteins in bacterial cells. These transcription regulators are responsible for many important cellular processes and are involved in pathogenesis of bacteria as well. The best known histone-like proteins, such as HU, FIS, H-NS and IHF, are often discussed. The most important findings in the HU protein researches are described in this minireview. Its roles in DNA compaction, shape modulation and negative supercoiling induction have been intensively studied. HU proteins regulate bacteria survival, growth, SOS response, virulence genes expression, cell division and many other cell processes. Elucidation of mechanism of HU protein action is subject of many research projects. This minireview gives a comprehensive overview of the HU protein.